The Attitudes of Elementary School Teachers to Eating Disorders - Adámková, Lenka (Tělesná výchova a výchova ke zdraví, 2020)
The publication describes the research on the attitudes of the teachers of health education or an equivalent course in lower secondary schools. In the theoretical part the issue is explained in a broader context. The types of eating disorders and the factors that contribute to the development of these disorders in childhood and adolescence are described. The following section explains the prevention of risk behaviour with a focus on the role of the school and teachers in the primary prevention of eating disorders. The publication describes how teachers can identify eating disorders and suggests their appropriate behaviour towards children with a suspected eating disorder. The book also focuses on the issue of attitudes. The text refers to relevant domestic and international research studies that illustrate the current state of the issue. The theoretical part of the publication defines the research problem, which is to identify the teachers' attitudes to eating disorders. The main research method is the semantic differential applied on a sample of 166 elementary school teachers from various regions of the Czech Republic. The additional method is the semi-structured interview conducted with some teachers from the research sample. The core focus of the publication is the new knowledge concerning the attitudes of elementary school teachers to eating disorders. The results are analysed in terms of the teachers' qualification, gender, age, and length of teaching experience. The final part of the paper summarizes the most important findings and recommendations for the prevention of eating disorders in educational practice. The new findings can also be applied in foreign educational systems.